Implementation of Halal Product Assurance in the Pharmaceutical Sector in Indonesia - Resti Dian Luthviati; Suviwat Jenvitchuwong (Lembaga Contrarius Indonesia, 2021)
The goal of this research is to determine and assess the implementation of halal certification for the pharmaceutical business in accordance with Law Number 33 of 2014 on Halal Product Assurance, as well as the variables that hinder and support its implementation. The impact of the JPH Law on the process value chain and supply chain of drugs and vaccines results in a total change in the pharmaceutical industry, including changes in ingredients resulting in reprocessing of quality, safety, and efficacy, changes in the distribution process, addition of personnel or staff, decreased economic capacity of the industry due to increased production costs, and there is a decrease in the industry's economic capacity due to increased costs of production. The halal status of a product has become a must-have for all consumers, particularly Muslims. Some parties, particularly the pharmaceutical business, continue to oppose to the existence of Law No. 33 of 2014 concerning Halal Product Guarantee. The supply of special facilities, such as rooms, equipment, and human resources, will significantly raise costs, resulting in higher drug prices and a reduction in people's access to the items they truly require for health care. Currently, the pharmaceutical sector must import 95 percent or more of its raw materials, totaling 150,000 items, in order to make about 30,000 different types of pharmaceuticals in the country.